Diurnal and Seasonal Flight Activity of the Honeybee, Apis Mellifera L, and its Relationship with Temperature, Light Intensity and Relative Humidity in the Savanna of Northern Nigeria (Global Journal of Science Frontier Research, 2013)
This study was carried out at Bauchi (10°19'N; 09°50'E; Elevation 520 m), Nigeria, and it was the first of its kind in the country. Number of foraging bees returning to the hive was recorded for five minutes, at intervals of 30 minutes, and used as an indicator of flight activity. Temperature, light intensity and relative humidity were recorded concurrently. Two peaks of flight activity (one just before sunrise and the other just before sunset), separated by a period of very low activity, were observed in the dry season. However, in the rainy season flight activity was high throughout the day, declining progressively towards sunset. Though there was no significant correlation (P>0.05) between flight activity and temperature at 25°C, an inverse and highly significant correlation (r=-0.75; P
Keywords: savanna; flight activity; foraging activity; apis mellifera; honeybee; temperature; light intensity; relative humidity; nigeria